Evaluation of the Impact of Water Pollution on Public Health and the Environment in Java Island - Kenny Kenny; Vernondo Horse; Jody Martin Ginting (LEADER: Civil Engineering and Architecture Journal, 2023)
Water pollution in Java Island is an urgent issue that has a serious impact on public health and the environment. Although several studies have been conducted, there are still gaps in the understanding of more specific health impacts and related environmental impacts. This study aims to comprehensively evaluate the impact of water pollution on the island of Java with a focus on public health and the environment. The literature review method is used to analyze and synthesize the relevant literature. The impact of water pollution on public health includes water-related diseases and chronic health problems. Impacts on the environment include damage to aquatic ecosystems and decreased biodiversity. The results and discussion of this study identify several previous studies that have been conducted in Java, but there is still a need for research that is more focused and holistic. This research provides a comprehensive picture of the impact of water pollution on the island of Java and provides a basis for developing policies and actions that are effective in reducing the negative impact.